2004
DOI: 10.1159/000079804
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine in the Prevention of Radiocontrast-Induced Nephropathy: Clinical Trials and End Points

Abstract: N-acetylcysteine (NAC) has been suggested to prevent radiocontrast-induced nephropathy (RCIN) in patients with a reduced renal function. However, clinical studies have not been demonstrating this effect consistently. Also, reviews and meta-analyses dealing with the question of prevention of RCIN by NAC have been controversial. Nearly all investigators used serum creatinine as surrogate end point of their trials, and changes in serum creatinine concentrations are thought to reflect the extent of renal injury as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 86 publications
1
9
0
1
Order By: Relevance
“…Thus, our data further support previous studies demonstrating the beneficial effects of NAC in renal failure and end-stage renal disease [24,28,40,41] and support the prophylactic value of the administration of NAC as a potential preventive strategy against CIN in subjects with chronic renal insufficiency. In addition, our present findings are in accordance with the recent report by Marenzi et al [42] who demonstrated that NAC reduced the severity of CIN in patients with acute myocardial infarction treated with primary angioplasty and had a more profound protective effect against CIN in patients with impaired renal function before the intervention and in patients with severely impaired left ventricular function.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, our data further support previous studies demonstrating the beneficial effects of NAC in renal failure and end-stage renal disease [24,28,40,41] and support the prophylactic value of the administration of NAC as a potential preventive strategy against CIN in subjects with chronic renal insufficiency. In addition, our present findings are in accordance with the recent report by Marenzi et al [42] who demonstrated that NAC reduced the severity of CIN in patients with acute myocardial infarction treated with primary angioplasty and had a more profound protective effect against CIN in patients with impaired renal function before the intervention and in patients with severely impaired left ventricular function.…”
Section: Discussionsupporting
confidence: 90%
“…23 In our study, the incidence of renal failure was low in both the groups and a total of 10% patients developed postoperative renal dysfunction (as defined by a postoperative rise in serum creatinine level of more than 25% from the preoperative value). The incidence of renal dysfunction did not differ between the groups (Table 3).…”
Section: Discussionmentioning
confidence: 50%
“…By contrast, in a recent study NAC reduced plasma creatinine values and estimated GFR, but had no effect on cystatin C levels, another marker of GFR, in volunteers with normal renal function suggesting a direct effect of NAC on plasma creatinine. [59,60], Regrettably, plasma creatinine was a surrogate end point in all trials published until now.…”
Section: Nacmentioning
confidence: 99%